PERANAN PEMBIAYAAN BSI KUR MIKRO DALAM PENINGKATAN KESEJAHTERAAN UMKM (STUDI KASUS BSI KCP NGAWI SUDIRMAN 1) - Prastika, Rima; Putri, Rizky Selvia (Fakultas Ekonomi Bisnis Islam, 2025)
The Micro, Small, and Medium Enterprises (MSME) sector plays a vital role in Indonesia’s economy but often faces major challenges, particularly limited business capital and access to affordable financing. In this context, Bank Syariah Indonesia (BSI), through its Sharia People's Business Credit (KUR) product—specifically BSI KUR Mikro—serves as a financing solution for MSME actors. This study aims to determine the role of BSI KUR Mikro financing in improving the welfare of MSMEs (A Study at Bank Syariah Indonesia KCP Ngawi Sudirman 1).The subjects of this research are employees in the financing department and BSI KUR Mikro financing customers at Bank Syariah Indonesia KCP Ngawi Sudirman 1, while the object of the research is the role of BSI KUR Mikro financing in improving the welfare of MSMEs at the same branch. This research is a qualitative case study using data collection techniques such as observation, interviews, and documentation conducted at Bank Syariah Indonesia KCP Ngawi Sudirman 1 to obtain relevant information.The results show that Bank Syariah Indonesia KCP Ngawi Sudirman 1 plays an important role in improving MSME welfare by providing business capital assistance to its customers. In addition, the bank also provides advice and recommendations for customers’ businesses. Bank Syariah Indonesia also carries out supervision to ensure that the financing aligns with the customers’ objectives. This has contributed to BSI’s success in improving the welfare of MSMEs, as indicated by the increase in customers’ income after receiving BSI KUR Mikro financing.